Study of Relationship between Anger, Self Efficiency, Coping Styles, Tendency to Narcotic Drug in a Group of Clients Dependent to Narcotic Drugs - Mohammad Oraki (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: Main purpose of the present research is the study of relationship between anger, self efficiency, coping styles, tendency to narcotic drug in a group of clients dependent to narcotic drugs. Methods: 180 men referred to Tehran City Aftab clinic who were diagnosed to be addicted on the basis of diagnostic criteria of DSMIV-TR and completed detoxification stage were selected by random sampling in accordance with an descriptive design .The clients were assessed with tests of self efficiency, coping styles, second form of state-trait anger expression scales and, Iranian scale of readiness for addiction. The results were analyzed with Pearson correlation coefficient test and stepwise regression analysis. Results: The results showed that there was a positive significant correlation between anger and tendency to narcotic drug, also there was significant correlation between emotional coping style and tendency to narcotic drug. Negative and significant correlation was found between self efficiency and tendency to narcotic drug. The results of stepwise regression analysis was showed self efficiency has been most effective predictor on tendency to narcotic drug. Conclusion: it seems that variabls such as self efficiency, anger and emotional coping style are most important predictors in tendency to narcotic drug use that should be special considered in next research and therapeutic intervention.